2015
DOI: 10.1175/jcli-d-14-00613.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Uncertainties in Future Projections of Seasonal Tropical Precipitation

Abstract: Projected changes in regional seasonal precipitation due to climate change are highly uncertain, with model disagreement on even the sign of change in many regions. Using a 20-member CMIP5 ensemble under the RCP8.5 scenario, the intermodel uncertainty of the spatial patterns of projected end-of-twenty-first-century change in precipitation is found not to be strongly influenced by uncertainty in global mean temperature change. In the tropics, both the ensemble mean and intermodel uncertainty of regional precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
175
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(189 citation statements)
references
References 44 publications
14
175
0
Order By: Relevance
“…Bush et al, 2015;Kim et al, 2016) to contributing to uncertainty in projections of future tropical rainfall (e.g. Kent et al, 2015). By examining the behaviour of modelled tropical rainfall at a wide range of spatial and temporal scales, we can hope to shed light on the way in which such biases develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bush et al, 2015;Kim et al, 2016) to contributing to uncertainty in projections of future tropical rainfall (e.g. Kent et al, 2015). By examining the behaviour of modelled tropical rainfall at a wide range of spatial and temporal scales, we can hope to shed light on the way in which such biases develop.…”
Section: Discussionmentioning
confidence: 99%
“…Levine and Turner, 2012) and can contribute to uncertainty in projections of future tropical rainfall (e.g. Kent et al, 2015). Deep convection parametrizations in these models often produce very intermittent rainfall at the level of the model's time step and gridscale, and also produce a poor representation of the processes and timing associated with the diurnal cycle of convection over land (e.g.…”
mentioning
confidence: 99%
“…We use output from simulations of the twentieth century and the twenty-first century [under the representative concentration pathway 8.5 (RCP8.5) emissions scenario] from 20 models [those used in Kent et al (2015, (Meehl et al 2007;Taylor et al 2012) (see Table 1). We consider both the MMM of the 20 chosen CMIP5 models and the spread of model projections across the 20-model ensemble, to address aims 1 and 2 and aim 3, respectively.…”
Section: A Datamentioning
confidence: 99%
“…Most previous analyses have focused on the MMM projected change quantities; however, Rowell et al (2015) highlighted the importance of understanding the mechanisms of change within individual models and concluded that further investigation should be aimed at developing expert judgment of process-based mechanisms and their reliability of projections (Rowell et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the projected population growth rate in Nigeria to 2050, 5.2%, is more than double that of the world average (1.9%) creating greater demand for water [11]. It should be noted that projected changes in seasonal rainfall due to climate change are highly uncertain [12]. Additionally, increased rainfall intensity generates greater run-off, limiting the amount available for use.…”
Section: Introductionmentioning
confidence: 99%